STRATIFICATION OF CRETACEOUS DEPOSITS OF THE SECTION № 29 – ZAKHIDNOОKTYABRSKA (KARKINITSKO-NORTH CRIMEAN TROUGH) BY PALYNOLOGICAL DATA - Shevchuk, O.; Pustovoitova, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Karkinitsko-North Crimean trough is a promising region of Ukraine for the search for hydrocarbons, and one of the main oil and gas complexes is the Cretaceous.Therefore, a detailed biostratigraphic subdivision of the Cretaceous sediments is important and necessary, which are the basis for further prospecting work and for the correlation of North Crimean trough with the similar age deposits of the adjacent regions. The Neocomian strata are especially problematic for subdivision and correlation. According to the results of the study of microphytofossils, the stratification of Cretaceous deposits of the Karkinitsko-North Crimean trough was carried out on the example of the supporting well № 29 – Zakhidnoоktyabrska. There are four spore-pollen complexes: Barremian, Aptian, Albian and Cenomanian. For the first time, the Cretaceous deposits were dissected according to the systematic composition of dinocysts, as well as the paleontological characteristics of sediments by other groups of microfossils – spores and pollen of higher plants, remnants of green algae, acritarchsand miсroforaminifers.